Geochemical Insights from Clinopyroxene Phenocrysts into the Magma Evolution of an Alkaline Magmatic System from the Sanshui Basin, South China - Peijia Chen (MDPI AG, 2021)
The Sanshui Basin is located at the northern continental margin of the South China Sea and characterized by a continental rift basin. The bimodal volcanic rocks in Sanshui Basin record the early Cenozoic magmatic activity in the South China Block, but the magmatic evolution that produced the bimodal volcanic rocks is poorly understood. Clinopyroxenes in bimodal volcanic rocks in the Sanshui Basin provide an opportunity to investigate magma during magma ascent. In this work, we classified nine types of clinopyroxene phenocrysts according to composition and texture in cogenetic basalt-trachyandesite-comenditic trachyte, while the composition of unzoned clinopyroxene have an evolution sequence of diopside-hedenbergite-aegirine along with an increase in trace element contents with a decrease of Mg#, indicating that the genesis of clinopyroxene was dominated by fractional crystallization in a closed magma system. However, the clinopyroxenes with reversed zoning and multiple zoning record the process of magma mixing and recharge indicating an open magma system. While fractional crystallization is the dominant process, magma mixing, recharge, and crystal settling were also found to influence magma evolution. Thermobarometric calculations showed that clinopyroxene crystallized a several structural levels in the crust during magma ascent. In this study, we established a magma plumbing system that provides new constraints for the magma evolution in the Sanshui Basin.